The Background and Use of Equine Imagery in Zechariah - Hahlen, Mark Allen (Stone-Campbell journal, 2000)
Equine imagery appears as a dominant motif at key locations in the book of Zechariah. Its use highlights the transformations that Yahweh will work out for his people and within his people. This study demonstrates how the placement and variations of the equine motif emphasize significant components of Zechariahs message. It also assists the reader to visualize and understand better those images in the Zechariah texts by presenting background information concerning horses in the ancient Persian and Hebrew milieus.